2004
DOI: 10.1007/s00709-004-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the actomyosin motor to the temperature-dependent translational diffusion of water by cytoplasmic streaming in Elodea canadensis cells

Abstract: The extent to which the actomyosin motor responsible for cytoplasmic streaming contributes to the translational diffusion of water in Elodea canadensis cells was studied by a nuclear magnetic resonance (NMR) spin-echo technique. The relative contribution of the actomyosin motor was determined from the corresponding apparent diffusion coefficient by the Einstein-Smolukhovsky relation. It is equal to the difference between the diffusional displacements of the cytoplasmic and the bulk water (deltaX). The NMR data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The obtained estimate of the velocity falls within the range of CS velocities determined by observation of the movement of chloroplasts in cells of E. canadensis leaves with the use of optical methods [5,7] and the movement of plant myosins along actin microfilaments [11]. This allows us to conclude that the functioning of the actomyosin complex leads to the involvement of the most of the cytosol water into the CS, along with organelles.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…The obtained estimate of the velocity falls within the range of CS velocities determined by observation of the movement of chloroplasts in cells of E. canadensis leaves with the use of optical methods [5,7] and the movement of plant myosins along actin microfilaments [11]. This allows us to conclude that the functioning of the actomyosin complex leads to the involvement of the most of the cytosol water into the CS, along with organelles.…”
supporting
confidence: 67%
“…It is also noteworthy that optical methods are inapplicable to most of nontransparent tissues. The diffusion NMR method [6,7], which permits tracing directly the translational displacement of water molecules, offers new possibilities of recording CSs. For example, NMR experiments on CS activation by temperature or Gd 3+ ions showed that the water diffusion coefficient in the cytoplasm of the cells of the Elodea canadensis stem was higher than that of pure water [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the prominent streaming of organelles, other processes are thought to involve acto-myosin dependent transport, including the movement of compounds and molecular targets that can not be visualised by light microscopy. For example, the translocation of water has recently been shown to be controlled by plant myosins [Vorob'ev et al, 2004] and targeting of cell wall pectins has been reported to be F-actin dependent [Baluška et al, 2002]. The movement of auxin, a crucial hormone for plant development, is believed to be directed by the actin-based deposition of membranous proteins [Baluška et al, 2003;Geldner et al, 2001;Muday et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The program presented in Figure 6 was used for selective assessment of water transport through apoplast of corn root [ 51 ] and cytoplasm of Elodea cells [ 52 , 53 ].…”
Section: Methodological Approaches To Selective Measurements Of Diffusionmentioning
confidence: 99%